Am I still human? Wearing an exoskeleton impacts self-perceptions of warmth, competence, attractiveness, and machine-likeness - Sandra Maria Siedl; Martina Mara (Computers in Human Behavior: Artificial Humans)
Occupational exoskeletons are body-worn technologies capable of enhancing a wearer's naturally given strength at work. Despite increasing interest in their physical effects, their implications for user self-perception have been largely overlooked. Addressing common concerns about body-enhancing technologies, our study explored how real-world use of a robotic exoskeleton affects a wearer's mechanistic dehumanization and perceived attractiveness of the self. In a within-subjects laboratory experiment, n = 119 participants performed various practical work tasks (carrying, screwing, riveting) with and without the Ironhand active hand exoskeleton. After each condition, they completed a questionnaire. We expected that in the exoskeleton condition self-perceptions of warmth and attractiveness would be less pronounced and self-perceptions of being competent and machine-like would be more pronounced. Study data supported these hypotheses and showed perceived competence, machine-likeness, and attractiveness to be relevant to technology acceptance. Our findings provide the first evidence that body-enhancement technologies may be associated with tendencies towards self-dehumanization, and underline the multifaceted role of exoskeleton-induced competence gain. By examining user self-perceptions that relate to mechanistic dehumanization and aesthetic appeal, our research highlights the need to better understand psychological impacts of exoskeletons on human wearers.